HLA class II gene associations in African American Type 1 diabetes reveal a protective HLA‐DRB1*03 haplotype. Issue 6 (21st March 2013) - Howson, J. M. M.; Roy, M. S.; Zeitels, L.; Stevens, H.; Todd, J. A.
Abstract Aims Owing to strong linkage disequilibrium between markers, pinpointing disease associations within genetic regions is difficult in European ancestral populations, most notably the very strong association of the HLA‐DRB1*03‐DQA1*05:01‐DQB1*02:01 haplotype with Type 1 diabetes risk, which is assumed to be because of a combination of HLA‐DRB1 and HLA‐DQB1. In contrast, populations of African ancestry have greater haplotype diversity, offering the possibility of narrowing down regions and strengthening support for a particular gene in a region being causal. We aimed to study the human leukocyte antigen (HLA) region in African American Type 1 diabetes. Methods Two hundred and twenty‐seven African American patients with Type 1 diabetes and 471 African American control subjects were tested for association at the HLA class II genes, HLA‐DRB1, HLA‐DQA1, HLA‐DQB1 and 5147 single nucleotide polymorphisms across the major histocompatibility complex region using logistic regression models. Population admixture was accounted for with principal components analysis. Results Single nucleotide polymorphism marker associations were explained by the HLA associations, with the major peak over the class II loci. The HLA association overall was extremely strong, as expected for Type 1 diabetes, even in African Americans in whom diabetes diagnosis is heterogeneous. In addition, there were unique features: the HLA‐DRB1*03 haplotype was split into HLA‐DRB1*03:01, which confers greatest susceptibility in these samples (odds ratio 3.17, 95% CI 1.72–5.83) and HLA‐DRB1*03:02, an allele rarely observed in Europeans, which confers the greatest protection in these African American samples (odds ratio 0.22, 95% CI 0.09–0.55). Conclusions The unique diversity of the African HLA region we have uncovered supports a specific and major role for HLA‐DRB1 in HLA‐DRB1*03 haplotype‐associated Type 1 diabetes risk.